Fiscal Transparency in Local Governments: Trends and Determinants: A Systematic Literature Review - Bengi, Biizni Putri; Maharani, Riantari; Fonna, Rizki Putri Nurita; Dinaroe, Dinaroe (Akbis: Media Riset Akuntansi dan Bisnis, 2025)
This study aims to analyze the development, determinants, and challenges of local government fiscal transparency during the period 2015–2025. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol, with 147 articles initially identified from the Scopus database and 20 articles meeting the inclusion criteria for detailed analysis. The results indicate that studies on local government fiscal transparency remain fragmented and unevenly distributed, with the majority conducted in developed countries, while evidence from developing countries is still limited. Eight main determinant groups were identified, namely local government size and characteristics, economic and fiscal conditions, political and institutional factors, public participation and oversight, performance and social conditions, technology and access to information, situational and crisis contexts, and spatial and external factors. Furthermore, the findings show that fiscal transparency is frequently implemented more in form than in substance, since disclosed information is not always presented in an accessible, comprehensive, and understandable way for the public.